A palaeontological model for determining the limits of early hominid taxonomic variability - Wood, Bernard (Bernard Price Institute for Palaeontological Research, 1991)
This paper has examined the utility and implications of using Australopithecus boisei as a model for assessing the limits of intraspecific variation in early hominid species. When compared to variation in a sample of lowland gorilla, the coefficient of variation values of the 25 cranial and mandibular, and 44 dental measurements taken on the A. boisei hypodigm were not excessive; the main difference between the two samples was the higher levels of canine variability within gorilla. Levels of variability in A. boisei were compared with those in the hypodigms of A. robustus and A. africanus. In neither case did comparisons demonstrate that those hypodigms were excessively variable. This suggests that if more than one taxon is present within these collections, then any differential diagnosis needs to be based on excessive variation in shape and not size.
Keywords: variation; australopithecine; morphometrics